Questioning Power: Deframing the STEM Discourse. Issue 2 (2nd April 2016) - Weinstein, Matthew; Blades, David; Gleason, Shannon C.
ABSTRACT: Internationally, STEM has become a slogan for organizing new discourses and practices in science education. In the form of a three-act play, we argue that STEM as social engineering orients and organizes school science education curriculum development in directions of scientific innovation and engineering that reinforce and legitimize a neoliberal hegemony of global competition and capitalist expansionism. The dialogue in the play presents an alternative conversation about the role of school science education amidst the sudden adoption of STEM. This conversation begins by examining the positivist assumption of STEM as societal salvation through the example of STEM in the invention, development, and deployment of new technologies, such as solar panels. The play then closely interrogates STEM as a curriculum orientation, shifting in the final act to possibilities for a different focus for science education curriculum development that includes interrogation and resistance to neoliberalism. RÉSUMÉ: Sur le plan international, les disciplines STEM sont une sorte de slogan servant à établir de nouveaux discours et de nouvelles pratiques en enseignement des sciences. Sous forme de pièce en trois actes, nous présentons les STEM comme une construction sociale qui oriente le développement des curriculums scientifiques scolaires vers des innovations scientifiques et d'ingénierie qui renforcent et légitiment une hégémonie néolibérale de concurrence globale et d'expansionnisme capitaliste. Le dialogue de notre pièce présente un discours différent sur le rôle de l'enseignement des sciences à l'école, dans un contexte d'adoption soudaine des STEM. Ce dialogue commence par analyser les tenants positivistes des STEM comme source de salut sociétal grâce aux exemples de STEM dans l'invention, le développement et la mise en application de nouvelles technologies, par exemple les panneaux solaires. La pièce se poursuit par un questionnement serré sur les disciplines STEM comme orientation des curriculums, et se termine, dans le troisième acte, par la possibilité de donner aux curriculums scientifiques à l'école un accent différent qui inclue une résistance au néolibéralisme.